Impact of possible methods to classify tangible assets in the accounting on the amount of depreciation. Example of selected sample of chemical company equipment - Pecinová, Zuzana; Lomnická, Dagmar (University of Pardubice, 2013)
Depreciations, such as a permanent reduction of the value of fixed assets, affect the profit and are an important source of investment financing. It is then important for businesses to select an appropriate depreciation policy in relation to the expected financial and income situation. An important part of the fixed assets of enterprises in the chemical industry are machinery and equipment (separate movable assets and sets of movable assets with a separate technical-economic purpose) that can be classified in different ways. Therefore, the aim of this paper is, by way of an example of a sample equipment, to analyse the implications of alternative classifications of this type of property in the amount of depreciation, then compare the impact of a specific method of repair in terms of replacing the whole equipment registered as a separate moveable asset or replacement of segments in the set of movable assets with a separate technical-economic purpose. At the end, selected possibilities of modernization will be analysed depending on the method to keep records of this type of property.